Guidance, Navigation, and Control Conference and Exhibit 1998
DOI: 10.2514/6.1998-4482
|View full text |Cite
|
Sign up to set email alerts
|

Final Approach Spacing Tool (FAST) velocity accuracy performance analysis

Abstract: The NASA passive Final Approach Spacing Tool (FAST) provides advisory information to the terminal air traffic controller for sequencing and merging of landing aircraft. It consists of the Trajectory Synthesizer (TS) and the Scheduling Logic (SL). FAST has undergone extensive field testing and performance evaluations of the FAST TS algorithms have been conducted. However, no analytical performance evaluations of the FAST SL logic have been performed to date. This paper evaluates the sensitivity of the FAST SL a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…As trajectory generation requirements continued to evolve based on the advanced descent and conflict prediction algorithms being researched, 17,18 the TS was rewritten again, this time in C++. This effort resulted in the Baseline TS with many of the benefits inherent with Object Oriented design, such as code reuse, code extensibility, and improved maintainability.…”
Section: A Trajectory Synthesizer Development Historymentioning
confidence: 99%
See 1 more Smart Citation
“…As trajectory generation requirements continued to evolve based on the advanced descent and conflict prediction algorithms being researched, 17,18 the TS was rewritten again, this time in C++. This effort resulted in the Baseline TS with many of the benefits inherent with Object Oriented design, such as code reuse, code extensibility, and improved maintainability.…”
Section: A Trajectory Synthesizer Development Historymentioning
confidence: 99%
“…19 Although the TS software has gone through many design iterations, its core trajectory algorithms have remained intact, providing a consistent platform to conduct research and support operational systems. The trajectory engine has been repeatedly validated through research, and operationally via the deployed TMA system 16,17,20 . The GenProf interface is the next phase of redesign of this software.…”
Section: A Trajectory Synthesizer Development Historymentioning
confidence: 99%
“…It is clear, however, that the ability of the surveillance system to deliver accurate, responsive speed estimates will be important to this application. Previous studies of the CTAS passive FAST decision support tool have shown that current generation alpha-beta trackers need to be replaced by modern tracking software to deliver the accuracy and reliability required for that tool [4]. It is anticipated that the Rh4S speed accuracy will then be on the order of 3 knots or better 131.…”
Section: Surveillance and Control Loop Assumptionsmentioning
confidence: 98%
“…The other surveillance issue is that of update rate, which determines tracker lag in speed estimates. Based on results in [4], we assume that good steady state speed values are obtained within 30 seconds after completing a deceleration transient. Increasing the sensor update rate to reduce tracker lag is also highly desirable.…”
Section: Surveillance and Control Loop Assumptionsmentioning
confidence: 99%